2004
DOI: 10.1177/0886260504269096
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Nonviolent, Psychologically Violent, and Physically Violent Male College Daters

Abstract: This brief report explores dating violence by comparing three groups of male college students (nonabusive, psychologically abusive only, and physically abusive). These men were compared on measures of impulsivity, problems with alcohol, life satisfaction, anger management skills, history of witnessing abuse, history of experiencing abuse, and relationship satisfaction. Data for this analysis were obtained from a sample of 115 male college students. Differences between the three groups of men were found in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 18 publications
3
44
0
3
Order By: Relevance
“…The findings of partner's use of physical aggression and low anger management skills predicting male violence are consistent with past research (Lundberg, Stith, Penn, & Ward, 2004;Marshall & Rose, 1990;White & Koss, 1991). However, the result indicating a high relationship satisfaction increases a male's use of physical aggression does not correspond to past research findings.…”
Section: Factors Predicting 12 <>supporting
confidence: 80%
“…The findings of partner's use of physical aggression and low anger management skills predicting male violence are consistent with past research (Lundberg, Stith, Penn, & Ward, 2004;Marshall & Rose, 1990;White & Koss, 1991). However, the result indicating a high relationship satisfaction increases a male's use of physical aggression does not correspond to past research findings.…”
Section: Factors Predicting 12 <>supporting
confidence: 80%
“…A small body of recent research has suggested that alcohol problems are positively associated with perpetration of aggressive and sometimes violent behavior in the dating relationships of college students (Follingstad et al, 1999;Lundeberg et al, 2004). In a study examining risk factors and correlates of dating violence among college students conducted by Follingstad and colleagues (1999), male college students who had perpetrated violence in their dating relationships reported more problems associated with alcohol use than those who had not perpetrated violence.…”
Section: Intimate Partner Violence Perpetration and Alcohol Problemsmentioning
confidence: 99%
“…Taking a break is a way of calming down, a "time out" that aids anger management, distancing oneself from others, etc. (Lundeberg, Stith, Penn and Ward 2004). By means of taking a break, people can stand back from complex issues, potential quarrels and unpleasantness and they can also get a new perspective on these problems (West, Watts, Trepal, Wester and Lewis 2001).…”
Section: Break Researchmentioning
confidence: 99%
“…Meaning, traditional media consumers as well as new media consumers might take some "time out" by means of media consumption whose chief aim is to take a break. Furthermore, since social research has related to taking a break as an activity having positive added value when it is necessary to deal with personal and public difficulty (Simister 2004;Lundeberg, Stith, Penn and Ward 2004;West, Watts, Trepal, Wester, and Lewis 2001;Dyson 2008;Golish and Powell 2003) it is clear that media breaks are a popular tool available for self-treatment. It seems than that when individuals are exposed to a variety of sources that do not fulfill their needs, complex structures are formed that generate weak cognition (Lang 2000;Fox 2004;Fox, Park and Lang 2007;Lang, Potter and Bolls 1999).…”
Section: In Conclusionmentioning
confidence: 99%